Electrocortical activity in a cognitive inhibition task immediately after maximum physical effort - Finkenzeller, T.; Doppelmayr, M.; Amesberger, G. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: The ability to inhibit irrelevant and to focus on relevant stimuli is essential for skilled performance in sports (Abernethy et al., 2007). Elite athletes have to perform well not only in the motor but also in the cognitive domain under maximum physical load and immediately afterwards. Up to now it is still unclear to what extent physical exertion influences basal cognitive processes and associated electrocortical (EEG) activity. The aim of the study was to analyse the time course of the impact of physical exertion on information processing speed in a cognitive inhibition task as assessed by the P300 of the event related potentials (ERP). Methods: A total of 14 sport students (4 f +10 m; age = 21.14 y; max. power: 4.56 W/kg) carried out a maximal graded exercise test on a cycle ergometer using a continuous incremental exercise protocol (initial power output: 30W f and 40W m; increment 15W f and 20W m each minute). A modified version of the Eriksen flanker (EF) task (Pontifex, & Hillman, 2007) was administered preceding (t1) and two times immediately after exhaustion (t2 and t3) as well as after a break of five minutes (t4). Reaction times (RT) and EEG was recorded and latency and amplitude of the P300 omponent of electrode positions Fz, C3, Cz, C4 P3, Pz and P4 were analysed. Results: For RT and for ERP, 2 (TASK: congruent vs. incongruent) x 4 (TIME) ANOVA-RM`s were calculated. Significant main effects in RT were obtained for TIME (F(3,39) = 5.08, p = .02, eta2 = .28) and TASK (F(1,13) = 222.17, p < .001, eta2 = .95). Post hoc analyses indicated that RT were significantly lower at t3 and t4 as compared to t1. Concerning to P300 latency, statistics revealed significant TIME effects for electrode positions C3, Cz, C4, Pz and P4. In comparison to t1, post hoc results demonstrated a significant decrease in latency at C3 and Cz for t3 and t4 as well as at C4 for all three post-exercise tasks. The P300 amplitude showed no significant exercise induced alterations. Discussion: Maximum physical exercise had a positive impact on information processing speed. The decrease of P300 latencies at central regions is well in line with improved information processing. It was expected that the P300 amplitude will increase after exercise in order to cope with the high physical stress while performing the EF task. However, the results do not indicate a higher allocation of attentional resources. Further studies are encouraged to research the impact of maximum physical loads on basal cognitive processes.